2020
DOI: 10.3389/fped.2020.584796
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Testicular Atrophy in Children With Testicular Torsion Following Emergent Orchiopexy

Abstract: Objective: To analyze the risk factors for testicular atrophy (TA) in children with testicular torsion (TT) following emergent orchiopexy. Methods: Clinical data of patients with TT undergoing orchiopexy were retrospectively reviewed, including age at surgery, affected side, delayed surgery (12–24 h and more than 24 h), echogenicity of testicular parenchyma on ultrasonography (ETPU), testicular blood flow on Color Doppler ultrasonography (CDUS), surgical findings (intraoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 19 publications
1
27
2
1
Order By: Relevance
“…The longest follow-up in this study was 198 months after salvage orchiopexy. The overall TA rate after orchiopexy was 56.6% compared with the previously reported TA rate range of 12.0%–68.0%, 8 9 while the severe TA rate was 41.5%, neither of which were sufficiently low for testicular salvageability. Furthermore, of the 27 patients who underwent reluctant orchiopexy who were surgically assessed as Arda grade III and inviable, 88.9% had their testes resected subsequently or atrophied during follow-up, and only 7.4% (2/27) had normal testicular volume and activity.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The longest follow-up in this study was 198 months after salvage orchiopexy. The overall TA rate after orchiopexy was 56.6% compared with the previously reported TA rate range of 12.0%–68.0%, 8 9 while the severe TA rate was 41.5%, neither of which were sufficiently low for testicular salvageability. Furthermore, of the 27 patients who underwent reluctant orchiopexy who were surgically assessed as Arda grade III and inviable, 88.9% had their testes resected subsequently or atrophied during follow-up, and only 7.4% (2/27) had normal testicular volume and activity.…”
Section: Discussionmentioning
confidence: 53%
“…These results are in accordance with those of previously published literature reports. 8 9 Furthermore, 98.1% (104/106) of orchiopexies had ipsilateral fixation of the affected testes, and 51.9% had contralateral exploration and fixation during the same operation. Additionally, 24.5% of torsed testes had bell clapper deformity, which was present in only 16.4% of contralateral explored testes and 10.9% of bilateral explored testes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Children need to be followed up for a long time after testicular torsion, and the testicular development is evaluated by ultrasound. Studies have reported that 38.94–41.4% of patients with testicular torsion who had undergone testicular fixation on the affected side eventually developed testicular atrophy ( 38 , 39 ). Yang et al ( 6 ) reported that among five patients with cryptorchid testicular torsion in whom the affected testis was retained, only one experienced postoperative ischemic atrophy, and the rest of the patients had normal testicular blood flow during follow-up.…”
Section: Discussionmentioning
confidence: 99%